Immersion in Computer Games: The Role of Spatial Presence and Flow. (5th January 2012) - Weibel, David; Wissmath, Bartholomäus
Abstract : A main reason to play computer games is the pleasure of being immersed in a mediated world. Spatial presence and flow are considered key concepts to explain such immersive experiences. However, little attention has been paid to the connection between the two concepts. Thus, we empirically examined the relationship between presence and flow in the context of a computer role-playing game (N = 70 ), a racing game (N = 120 ), and a jump and run game (N = 72 ). In all three studies, factor analysis revealed that presence and flow are distinct constructs, which do hardly share common variance. We conclude that presence refers to the sensation of being there in the mediated world, whereas flow rather refers to the sensation of being involved in the gaming action. Further analyses showed that flow and presence depend on motivation and immersive tendency. In addition, flow and presence enhanced performance as well as enjoyment.